History and clinical examination at a glance - Gleadle, Jonathan (Chichester, West Sussex : Wiley-Blackwell, 2012)
Every medical student must be able to take an accurate history and perform a physical examination. This third edition of History and Clinical Examination at a Glance provides a concise, highly illustrated companion which will help you develop these critical skills as you practice on the wards
Includes index
Revised edition of: History and examination at a glance / Jonathan Gleadle. 2nd ed. c2007
Revised edition of: History and examination at a glance/Jonathan Gleadle. 2nd ed. c2007
Keywords: Medical history taking -- Handbooks, manuals, etc; Physical diagnosis -- Handbooks, manuals, etc; Medical History Taking -- Handbooks; Physical Examination -- Handbooks